Pengembangan Instrumen Tes Kemampuan Berpikir Kritis Matematis Materi SPLDV pada Siswa SMP - Intan Nur Ro'in Wijayanti; Zaki Ahmad Fauzan (MASALIQ, 2026)
Junior high school students’ mathematical critical thinking skills remain relatively low, particularly when solving problems involving Systems of Linear Equations in Two Variables (SPLDV). This condition is associated with instructional practices that remain oriented toward routine calculation procedures and the search for a single correct answer, thereby failing to optimally develop students’ reasoning, evaluation of assumptions, and problem-solving processes. This study aims to develop a valid, practical, and effective test instrument for assessing mathematical critical thinking skills in SPLDV among students at SMP YPM 3 Taman Sidoarjo. The instrument development refers to six indicators of mathematical critical thinking skills, namely Focus for identifying problems, Reason for providing justification, Inference for drawing conclusions, Situation for applying concepts, Clarity for communicating the solution process, and Overview for reviewing answers. The developed instrument is designed to systematically measure students’ abilities in each indicator and to function as a diagnostic tool for identifying their strengths and weaknesses. Thus, this instrument is expected to support teachers in obtaining more accurate information regarding students’ mathematical critical thinking profiles and to serve as a basis for designing more effective, targeted, and needs-based instructional strategies and interventions.